2002
DOI: 10.1042/bj20020567
|View full text |Cite
|
Sign up to set email alerts
|

Ance, a Drosophila angiotensin-converting enzyme homologue, is expressed in imaginal cells during metamorphosis and is regulated by the steroid, 20-hydroxyecdysone

Abstract: Ance is a single domain homologue of mammalian angiotensin-converting enzyme (ACE) and is important for normal development and reproduction in Drosophila melanogaster. Mammalian ACE is responsible for the synthesis of angiotensin II and the inactivation of bradykinin and N -acetyl-Ser-Asp-Lys-Pro, but the absence of similar peptide hormones in insects suggests novel functions for Ance. We now provide evidence in support of a role for Ance during Drosophila metamorphosis. The transition of larva to pupa was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Quan et al (1998) reported that BmAcer expression is ecdysone-inducible. A 20E-induced synthesis of ACE-like activity was also observed in D. melanogaster (Siviter et al, 2002) and in A. stephensi (Ekbote et al, 1999). Moreover, Loeb et al (1998) demonstrated that ACE-activity stimulates ecdysteroid synthesis, perhaps due to feedback effects.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Quan et al (1998) reported that BmAcer expression is ecdysone-inducible. A 20E-induced synthesis of ACE-like activity was also observed in D. melanogaster (Siviter et al, 2002) and in A. stephensi (Ekbote et al, 1999). Moreover, Loeb et al (1998) demonstrated that ACE-activity stimulates ecdysteroid synthesis, perhaps due to feedback effects.…”
Section: Discussionmentioning
confidence: 69%
“…Siviter et al (2002) previously suggested such a role for ACE based on their findings that larvalpupal transition of D. melanogaster was accompanied by a 3-fold increase in ACE-activity. This increase was attributed to the strong induction of Ance expression in the imaginal cells by 20E.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The first was matched to ACE (peptidyl dipeptidase A, EC 3.4.15.1), a member of the M2-metallopeptidase family, and was demonstrated in the in-solution digested sample and in the 110-and 100-kDa bands of the 1-DE secreted saliva. ACE have been described as nonspecific dipeptydyl carboxypeptidases [28] and have been characterised in a number of insects, including Bombyx mori, D. melanogaster, L. migratoria, Musca domestica, and S. littoralis [29][30][31][32][33]. In insects, ACE are thought to be involved in regulating peptide hormones and neuropeptides by removing dipeptides, dipeptideamides and tripeptideamides from the C terminus of short peptides ( [31,32,34,35], reviewed in [36]).…”
Section: Discussionmentioning
confidence: 99%